Association of serum C1q tumour necrosis factor–related protein 9 with the severity of lower extremity peripheral arterial disease in type 2 diabetes patients. (May 2018) - Jiang, Wengao; Tang, Qiang; Zhang, Lei; Chao, Yinxue; Hong, Bing
Objective: Recent studies have indicated the implication of C1q tumour necrosis factor–related protein 9 in vascular pathology of atherosclerosis. This study first investigated the association of C1q tumour necrosis factor–related protein 9 and the severity of lower extremity peripheral arterial disease in type 2 diabetes mellitus patients. Methods: A total of 200 patients with type 2 diabetes mellitus had ankle–brachial index examined in this cross-sectional study, 60 patients with ankle–brachial index of ⩽0.9 were diagnosed with peripheral arterial disease and further classified into mild, moderate and severe group with Vivid 7 diagnostic apparatus. Results: C1q tumour necrosis factor–related protein 9 and adiponectin were higher in diabetes mellitus with severe peripheral arterial disease than diabetes mellitus with mild and moderate peripheral arterial disease groups. After adjustment of conventional atherosclerosis risk factors, C1q tumour necrosis factor–related protein 9 ( r = −0.627, p  < 0.001) and adiponectin ( r = −0.431, p = 0.003) were negatively correlated with the severity of peripheral arterial disease. Logistic regression analysis showed C1q tumour necrosis factor–related protein 9 was independently associated with the severity of peripheral arterial disease (odds ratio = 0.272, 95% confidence interval = 0.08–0.927, p = 0.037). Conclusion: Serum C1q tumour necrosis factor–related protein 9 is negatively and independently associated with the severity of peripheral arterial disease in type 2 diabetes mellitus patients, suggesting the protective potentials of C1q tumour necrosis factor–related protein 9 in the progression of peripheral arterial disease in human type 2 diabetes mellitus.